Pengaruh pengetahuan perpajakan, kesadaran wajib pajak dan sanksi pajak terhadap kepatuhan wajib pajak dalam membayar Pajak Bumi dan Bangunan di Kecamatan Pulau Batang Dua Kota Ternate - Malendes, Daniel; Sabijono, Harijanto; Weku, Priscillia (Yayasan Widyantara Nawasena Raharja, 2024)
Taxes are mandatory contributions to the State owed by individuals or entities that are coercive by law, by not receiving direct compensation and used for the benefit of the State for the greatest possible prosperity of the people. This study aims to analyze the influence of understanding of taxation, awareness of tax payers, and tax sanctions on taxpayer compliance in paying land and building taxes in Pulau Batang Dua sub-district, Ternate city, North Maluku Province. Researchers used a quantitative descriptive technique. The data used in the form of primary data using a questionnaire. The statistical method used is multiple regression analysis. The test results show that partially understanding of taxation has no significant effect on taxpayer compliance, taxpayer awareness has a significant effect on taxpayer compliance, tax sanctions have a significant effect on taxpayer compliance, and simultaneously understanding of taxation, taxpayer awareness, and sanctions taxes have a significant effect on taxpayer compliance.